Cajo Cornelio Tacito - Tacitus, Publius Cornelius, 55-120. (Firenze Firenze)
<4> cilt (1. c. lvi, 329, lxxi sayfa ; 3. c. 361, lii sayfa ; 4. c. 401, xxxii sayfa ; 5. c. 173, xxvii, [2], xxxii, 171, xxxiii sayfa)